2013
DOI: 10.1016/j.anorl.2012.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Neck and mediastinal node dissection in pharyngolaryngeal tumors

Abstract: In the present series, advanced laryngeal carcinoma was never associated with positive SM nodes, whereas advanced hypopharyngeal carcinoma showed a trend in favor of paratracheal lymph node involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
8
1
Order By: Relevance
“…7,9 Dequanter et al also concluded that primary tumors with PS apex invasion, or tumor diameter exceeding 3.5 cm showed a trend in favor of paratracheal lymph node involvement. 17 In contrast, the present study showed that primary tumors originating from PPW or PPW invasion showed a correlation with retropharyngeal node involvement. In agreement with pre- With low LMRs ranging from 0% to 5.1%, levels I and V were considered low risk.…”
Section: Discussioncontrasting
confidence: 97%
“…7,9 Dequanter et al also concluded that primary tumors with PS apex invasion, or tumor diameter exceeding 3.5 cm showed a trend in favor of paratracheal lymph node involvement. 17 In contrast, the present study showed that primary tumors originating from PPW or PPW invasion showed a correlation with retropharyngeal node involvement. In agreement with pre- With low LMRs ranging from 0% to 5.1%, levels I and V were considered low risk.…”
Section: Discussioncontrasting
confidence: 97%
“…Weber et al [64] found level VIb metastases in 18% of laryngeal carcinomas, and 27% in case of subglottic extension. Level VIb metastases carry a high risk for subsequent metastasis to the superior mediastinum [65].…”
Section: Larynx (Table 4)mentioning
confidence: 99%
“…The author concluded that because high rate of involvement and recurrence of level VIb, systematic elective bilateral neck dissection might be needed. Previous retrospective studies [20,21] indicated that pyriform sinus apex or postcricoid invasion, or tumor diameter exceeding 3.5cm showed a trend in favor of paratracheal lymph node involvement. In our previous study, esophagus invasion was also highly correlated with increased risk of developing level VIb metastasis.…”
Section: Discussionmentioning
confidence: 96%